4x-y=32y=-2x+70 Try rearraging it. If they're all equal, then the order does not matter.2x+70=4x-y=32y-4x,-4x,+y,+y-2x+70=33y-x+35=33y
2y+8y2 can be factored to 2y(1+4y)
4(3x-8y = 24) 12x+32y = 96 Multiply all terms in the first equation by 4: 12x-32y = 96 12x+32y = 96 Add both equations together: 24x = 192 Divide both sides by 24 to find the value of x: x = 8 Substitute the value of x into the original equations to find the value of y: Therefore: x = 8 and y = 0
8y2-10y-3 8y2-12y+2y-3 4y(2y-3)+1(2y-3) (4y+1)(2y-3)
The sum equals the product.
the sum of 18 and a number equals 24
The expression can be factored as -12x + 32y -16z = 4(-3x + 8y - 4z) but a slightly improved presentation would be to extract -4 from the original expression. So, -12x + 32y -16z = -4(3x - 8y + 4z)
Yes they are.